A Call to Develop Course-Based Undergraduate Research Experiences (CUREs) for Nonmajors Courses - Ballen, Cissy J. (CBE Life Sci Educ, 2017)
Course-based undergraduate research experiences (CUREs) for non–science majors (nonmajors) are potentially distinct from CUREs for developing scientists in their goals, learning objectives, and assessment strategies. While national calls to improve science, technology, engineering, and mathematics education have led to an increase in research revealing the positive effects of CUREs for science majors, less work has specifically examined whether nonmajors are impacted in the same way. To address this gap in our understanding, a working group focused on nonmajors CUREs was convened to discuss the following questions: 1) What are our laboratory-learning goals for nonmajors? 2) What are our research priorities to determine best practices for nonmajors CUREs? 3) How can we collaborate to define and disseminate best practices for nonmajors in CUREs? We defined three broad student outcomes of prime importance to the nonmajors CURE: improvement of scientific literacy skills, proscience attitudes, and evidence-based decision making. We evaluated the state of knowledge of best practices for nonmajors, and identified research priorities for the future. The report that follows is a summary of the conclusions and future directions from our discussion.